Enhanced brain targeting efficacy of Olanzapine through solid lipid nanoparticles. (17th February 2017) - Natarajan, Jawahar; Baskaran, Mahendran; Humtsoe, Lireni C.; Vadivelan, R.; Justin, A.
Abstract: Olanzapine (OLZ) is a typical anti-psychotic drug, which is highly lipophilic in nature, belongs to Biopharmaceutical Classification System (BCS) class II category. Though OLZ is an effective agent in the treatment of Schizophrenia, but it exhibits poor bioavailability (57%) due to extensive first-pass metabolism resulted in high dose is required to achieve therapeutic concentration in brain. Emerging evidences are indicating that high dose administration of OLZ may cause Extrapyramidal symptoms (EPS) in the psychotic patients. Hence, the present study is designed to develop Olanzapine solid lipid (OLZ-SLNs) using minimal dose of OLZ thereby enhancing the brain efficacy as well as to reduce the side effects associated with OLZ. OLZ-SLNs have been prepared by "solvent diffusion method" using lipids, such as glyceryl monostearate (GMS), tripalmitin (TP), Tween 80, and Stearyl amine as positive charge inducer. The prepared OLZ-SLNs were subjected to particle size analysis, zeta potential, and poly dispersity index measurement by using Malvern Zetasizer. Pharmacokinetics assessments of OLZ-SLNs were carried in conscious male Wistar rats through intravenous administration. Results have shown that average particle size and zeta potential of SLNs of GMS and TP were ranged from 165.1 ± 2.2 to 110.5 ± 0.5 and 35.29 ± 1.2 and 66.50 ± 0.7 mV, respectively. Relative bioavailability of OLZ in the brain was increased up to 23-fold and clearance was decreased when OLZ-SLNs while administrated intravenously. The area under the curve (AUC) and mean residence time (MRT) of OLZ-SLNs in brain were higher than OLZ suspension. These results indicate that SLNs are a promising drug delivery for OLZ. It may be an effective tool to enhance the bioavailability of OLZ in the brain with less dose administration, which could reduce the EPS associated with OLZ.